THE WAYS OF LEARNING PHRASEOLOGICAL UNITS WITH COMPONENTS EXPRESSING MONEY UNITS IN TEACHING PROCESS (E Conference Zone, 2022)
This article is dedicated to the analysis of phraseological units with component denoting “money” and teaching phraseological units to students. The field of phraseology in any language is so varied and fascinating that one could spend an entire lifetime considering and analyzing it from various viewpoints. The author will analayze in the following article the best ways of learning phraseological units both effective and efficient for learners.